Efficacy, safety, and tolerability of secukinumab in patients with active ankylosing spondylitis: a randomized, double-blind phase 3 study, MEASURE 3 - Pavelka, Karel; Kivitz, Alan; Dokoupilova, Eva; Blanco, Ricardo; Maradiaga, Marco; Tahir, Hasan; Pricop, Luminita; Andersson, Mats; Readie, Aimee; Porter, Brian (Arthritis research & therapy, 2017)
BACKGROUND: Secukinumab, an anti-interleukin-17A monoclonal antibody, improved the signs and symptoms of ankylosing spondylitis (AS) in two phase 3 studies (MEASURE 1 and MEASURE 2). Here, we present 52-week results from the MEASURE 3 study assessing the efficacy and safety of secukinumab 300 and 150 mg subcutaneous maintenance dosing, following an intravenous loading regimen. METHODS: A total of 226 patients were randomized to intravenous secukinumab 10 mg/kg (baseline, weeks 2 and 4) followed by subcutaneous secukinumab 300 mg (IV-300 mg) or 150 mg (IV-150 mg) every 4 weeks, or matched placebo. Patients in the placebo group were re-randomized to subcutaneous secukinumab at a dose of 300 or 150 mg at week 16. The primary endpoint was the Assessment of SpondyloArthritis international Society criteria for 20% improvement (ASAS20) response rate at week 16 in the IV-300 mg or IV-150 mg versus placebo. Other endpoints assessed through week 52 included improvements in ASAS40, ASAS 5/6, Bath Ankylosing Spondylitis Disease Activity Index, and ASAS partial remission responses, as well as the change from baseline in high-sensitivity C-reactive protein levels. Statistical analyses followed a predefined hierarchical hypothesis testing strategy to adjust for multiplicity of testing, with non-responder imputation used for binary variables and mixed-model repeated measures for continuous variables. RESULTS: The primary efficacy endpoint was met; the ASAS20 response rate was significantly greater at week 16 in the IV-300 mg (60.5%; P < 0.01) and IV-150 mg (58.1%; P < 0.05) groups versus placebo (36.8%). All secondary endpoints were met at week 16, except ASAS partial remission in the IV-150 mg group. Improvements achieved with secukinumab in all clinical endpoints at week 16 were also sustained at week 52. Infections, including candidiasis, were more common with secukinumab than with placebo during the placebo-controlled period. During the entire treatment period, pooled incidence rates of Candida infections and grade 3-4 neutropenia were 1.8% for both of these adverse events in secukinumab-treated patients. CONCLUSIONS: Secukinumab (300 mg and 150 mg dose groups) provided rapid, significant and sustained improvement through 52 weeks in the signs and symptoms of patients with AS. The safety profile was consistent with previous reports, with no new or unexpected findings. TRIAL REGISTRATION: ClinicalTrials.gov, NCT02008916 . Registered on 8 December 2013. EUDRACT 2013-001090-24. Registered on 24 October 2013). The study was not retrospectively registered.
Keywords: Dose-Response Relationship, Drug; antirevmatika; Injections, Subcutaneous; Male; Female; Middle Aged; intravenózní podání; Double-Blind Method; injekce subkutánní; Antibodies, Monoclonal; Antirheumatic Agents; mužské pohlaví; ankylózující spondylitida; ženské pohlaví; Adult; Administration, Intravenous; Interleukin-17; Spondylitis, Ankylosing; dospělí; lidé středního věku; monoklonální protilátky; dvojitá slepá metoda; interleukin-17; lidé; Humans; vztah mezi dávkou a účinkem léčiva